Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12966-016-0408-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal feeding practices and fussy eating in toddlerhood: a discordant twin analysis

Abstract: BackgroundParental feeding practices are thought to play a causal role in shaping a child’s fussiness; however, a child-responsive model suggests that feeding practices may develop in response to a child’s emerging appetitive characteristics. We used a novel twin study design to test the hypothesis that mothers vary their feeding practices for twin children who differ in their ‘food fussiness’, in support of a child-responsive model.MethodsParticipants were mothers and their 16 month old twin children (n = 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
3
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 38 publications
3
59
3
3
Order By: Relevance
“…While there is no consensus on the definition of ‘fussy’ eating, which makes it difficult to ascertain prevalence, parents’ perceptions of fussiness, as measured in the present study, are equally important . That is, perceptions of ‘fussiness’ are understood to result in alterations in parents–child feeding interactions, such that parents are more inclined to use non‐responsive feeding practices which in turn have been seen to increase fussy behaviours . Given this, parents who simply perceive child feeding difficulties, are likely to benefit from child feeding interventions which focus on use of responsive feeding strategies.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…While there is no consensus on the definition of ‘fussy’ eating, which makes it difficult to ascertain prevalence, parents’ perceptions of fussiness, as measured in the present study, are equally important . That is, perceptions of ‘fussiness’ are understood to result in alterations in parents–child feeding interactions, such that parents are more inclined to use non‐responsive feeding practices which in turn have been seen to increase fussy behaviours . Given this, parents who simply perceive child feeding difficulties, are likely to benefit from child feeding interventions which focus on use of responsive feeding strategies.…”
Section: Discussionmentioning
confidence: 86%
“…21,22 That is, perceptions of 'fussiness' are understood to result in alterations in parents-child feeding interactions, such that parents are more inclined to use non-responsive feeding practices which in turn have been seen to increase fussy behaviours. 23,24 Given this, parents who simply perceive child feeding difficulties, are likely to benefit from child feeding interventions which focus on use of responsive feeding strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A reverse relationship also pertained, but the temporal association from child to parent was stronger. A large within-family study of preschool twins showed that parents varied their pressuring feeding style when their twins were discordant for food fussiness 29 . The fussier twin was pressured more than their co-twin, also in support of a child-driven model of parental feeding behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to significant genetic underpinnings, there are also strong environmental determinants of feeding problems or fussy eating, particularly the feeding practices (Harris et al, 2016) that parents use. Much research has established the importance of early feeding behaviour and a high quality…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Practices such as restriction and pressure to eat can have unintended negative consequences for children's eating (Birch, Fisher, & Davison, 2003;Galloway, Fiorito, Francis, & Birch, 2006;Ogden, Cordey, Cutler, & Thomas, 2013) whereas practices such as monitoring of child food intake can have positive outcomes such as reduced non-nutritive food choices (Klesges, Stein, Eck, Isbell, & Klesges, 1991;Musher-Eizenman & Holub, 2007). It is also important to note that several studies have found parental feeding practices to be the result of child characteristics and behaviours, rather than the cause, or have found bidirectional relationships in feeding interactions (Demir et al, 2012;Harris et al, 2016;Hodges et al, 2013). Therefore, it is important to examine the relationship between the MCHFS and parental report of feeding practices early in life, when complementary feeding is becoming established.…”
Section: The Montreal Children's Hospital Feeding Scalementioning
confidence: 99%